The Effects of Developing an Integrated Home Pharmaceutical Care system for Elderly Community-Dwelling Individuals with Type 2 Diabetes mellitus and Depression San Sai District, Chiang Mai Province - อินทจักร์ ณภัทร (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
Abstract This quasi-experimental research aims to 1) compare the level of depression in elderly patients with Type 2 diabetes and comorbid depression before and after receiving the integrated home-based pharmaceutical care; 2) compare plasma glucose levels between the experimental and control groups of elderly patients with Type 2 diabetes and comorbid depression in the community. The sample consisted of 24 elderly outpatients diagnosed with Type 2 diabetes and comorbid depression at San Sai Hospital, Chiang Mai Province. The sample was divided into experimental and control groups, each consisting of 12 participants. Data collection tools included the 9Q Depression Assessment Questionnaire, an adherence assessment for antidepressant medications in patients with mental health conditions, a medication adherence questionnaire for diabetes and comorbid conditions from San Sai Hospital, and a plasma glucose level recording form. Data were analyzed using descriptive statistics, compare the equality of two independent population groups with a test of the mean, and analyze the comparison of the means between two groups of samples, both independent and dependent. The research findings revealed that elderly patients with type 2 diabetes and comorbid depression, after receiving integrated home pharmaceutical care. The experimental group demonstrated a statistically significant reduction in depression severity and plasma glucose levels compared to the control group (p < 0.05).(t = 6.76 and 2.21 respectively) Keywords: Elderly patients with type 2 diabetes, Depression, Integrated home pharmaceutical care system